2018
DOI: 10.1186/s12872-018-0929-7
|View full text |Cite
|
Sign up to set email alerts
|

Native valve endocarditis due to Escherichia coli infection: a case report and review of the literature

Abstract: BackgroundInfective endocarditis due to Escherichia coli is a rare disease but is increasing in frequency, especially among older women. In addition, its mortality rate is higher than that of endocarditis due to the HACEK-group gram-negative bacteria (Haemophilus spp., Aggregatibacter spp., Cardiobacterium hominis, Eikenella corrodens, and Kingela spp.).Case presentationA 58-year-old Japanese woman with a history of alcohol abuse was admitted to our hospital because of a fever. She was diagnosed with infective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 32 publications
0
61
0
Order By: Relevance
“…On the other hand, E. coli is often the main culprit of infections in the gastrointestinal tract [ 8 ], as well as other parts of human and animal organisms [ 9 , 10 ]. In more precise terms, E. coli typically causes urinary infections [ 11 , 12 ], but it can also lead to many other serious infections and conditions, such as: appendicitis [ 13 ], pneumonia [ 14 ], meningitis [ 15 ], endocarditis [ 16 ], gastrointestinal infections [ 17 ], etc. Research findings have shown us that E. coli can cause infections in all age groups and those infections can be acquired in the general population, i.e., community-acquired, as well as related to healthcare institutions [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, E. coli is often the main culprit of infections in the gastrointestinal tract [ 8 ], as well as other parts of human and animal organisms [ 9 , 10 ]. In more precise terms, E. coli typically causes urinary infections [ 11 , 12 ], but it can also lead to many other serious infections and conditions, such as: appendicitis [ 13 ], pneumonia [ 14 ], meningitis [ 15 ], endocarditis [ 16 ], gastrointestinal infections [ 17 ], etc. Research findings have shown us that E. coli can cause infections in all age groups and those infections can be acquired in the general population, i.e., community-acquired, as well as related to healthcare institutions [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 With the exception of the HACEK organisms (ie, Haemophilus, Aggregatibacter, Cardiobacterium, Eikenella, and Kingella), Mitral valve is the most common site of infection (Table 1). 6,7 Mortality rates of 53% to 65% have been reported in patients with E coli endocarditis. 6,7 Although E coli does not stick to native heart valves as easily as staphylococci and streptococci, 8 it does cause PVE and has been reported with a frequency as high as 19%, in 7 of 37 cases of all cause endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Mortality rates of 53% to 65% have been reported in patients with E coli endocarditis. 6,7 Although E coli does not stick to native heart valves as easily as staphylococci and streptococci, 8 it does cause PVE and has been reported with a frequency as high as 19%, in 7 of 37 cases of all cause endocarditis. 6 Some of the risk factors associated with infections caused by ESBL producing organisms are advanced age, female gender, diabetes mellitus, prolonged hospital stay, prior exposure to cephalosporins, quinolones, and 3 or more courses of antibiotic therapy in the preceding year.…”
Section: Discussionmentioning
confidence: 99%
“… 14 It does occur more commonly in prosthetic valves and previous systematic review reveals 52% has a urinary source as with our patient and up to a third are considered nosocomial in nature. 14 , 15 The mortality is high (21%). 15 Registry studies suggest the occurrence of intracardiac abscess with non-HACEK infection to be 42%.…”
Section: Discussionmentioning
confidence: 99%